Sekundárne dyslipidémie - Vargová, V; Pytliak, M; Mechírová, V (Vnitrni lekarstvi, 2012)
Dyslipidemias rank among the most important preventabile factors of atherogenesis and its progression. This topic is increasingly being discussed as e.g. more than 50% of Slovak population die on atherosclerotic complications. According to etiology we distinguish primary dyslipidemias with strictly genetic background and secondary ones with origin in other disease or pathological state. Secondary dyslipidemias accompany various diseases, from common (endocrinopathies, renal diseases etc) to rare ones (thesaurismosis etc.) and represents one of symptoms of these diseases. Apart from particular clinical follow up of diagnosed dysipidemias, basic screening and secondary causes as well as treatment due to updated guidelines is recuired. In this review we present the most frequent dyslipidemias of clinical practice.
Keywords: Dyslipidemias; lidé; Humans; dyslipidemie